Sosialisasi Perancangan Prototype Sistem Absensi Pegawai Menggunakan Metode Prototyping pada Dinas Kearsipan Provinsi Sumatera Selatan - Derta Octara; Andri, Andri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to design a prototype of a digital-based employee attendance system using the Prototyping method at the South Sumatra Provincial Archives Office as an effort to improve the accuracy, efficiency, and transparency of attendance administration. The background of this study is based on the problems of manual attendance, which is prone to recording errors, data manipulation, and requires a long time in the report recapitulation process. The research method used is applied with stages of gathering requirements through observation and mockup interface design, prototype development, and functional testing using Black Box Testing. The results show that the designed attendance system prototype is capable of performing its main functions optimally, particularly in the geolocation validation feature to ensure that employees are present within the office radius, the prevention of double attendance, and the automation of attendance data recording. The discussion confirms that the application of the Prototyping method facilitates the adjustment of the system to user requirements from the early stages of development. In conclusion, the resulting attendance system prototype is considered feasible as the basis for developing the final system to support more effective and accountable personnel management.